Body fluid from the parasitic worm Ascaris suum inhibits broad‐acting pro‐inflammatory programs in dendritic cells. Issue 3 (3rd December 2019) - Arora, Pankaj; Moll, Janne Marie; Andersen, Daniel; Workman, Christopher Thomas; Williams, Andrew R.; Kristiansen, Karsten; Brix, Susanne
Summary: Dendritic cells (DCs) are essential for generating T‐cell‐based immune responses through sensing of potential inflammatory and metabolic cues in the local environment. However, there is still limited insight into the processes defining the resultant DC phenotype, including the type of early transcriptional changes in pro‐inflammatory cues towards regulatory or type 2 immune‐based cues induced by a variety of exogenous and endogenous molecules. Here we compared the ability of a selected number of molecules to modulate the pro‐inflammatory phenotype of lipopolysaccharide (LPS) and interferon‐ γ (IFN‐ γ )‐stimulated human monocyte‐derived DCs towards an anti‐inflammatory or regulatory phenotype, including Ascaris suum body fluid [helminth pseudocoelomic fluid (PCF)], the metabolites succinate and butyrate, and the type 2 cytokines thymic stromal lymphopoietin and interleukin‐25. Our data show that helminth PCF and butyrate treatment suppress the T helper type 1 (Th1)‐inducing pro‐inflammatory DC phenotype through induction of different transcriptional programs in DCs. RNA sequencing indicated that helminth PCF treatment strongly inhibited the Th1 and Th17 polarizing ability of LPS + IFN‐ γ ‐matured DCs by down‐regulating myeloid differentiation primary response gene 88 (MyD88)‐dependent and MyD88‐independent pathways in Toll‐like receptor 4 signaling. By contrast, butyrate treatment had a strong Th1‐inhibiting action, and transcripts encoding important gut barrier defending factors such as IL18, IL1B and CXCL8 were up‐regulated. Collectively, our results further understanding of how compounds from parasites and gut microbiota‐derived butyrate may exert immunomodulatory effects on the host immune system. Abstract : This study examines the immunoregulatory potential of different exogenous and endogenous molecules on pro‐inflammatory human monocyte‐derived dendritic cells (moDCs) with the focus of identifying early transcriptional regulators of pro‐inflammatory cues. Body fluid from Ascaris suum was found to potently down‐regulate specific T helper type 1‐ and type 17‐related pathways in pro‐inflammatory moDCs, which overlapped, but also segregated from those induced by the intestinal metabolite butyrate. These results improve our understanding of how compounds from parasites may exert immunomodulatory effects on the host immune system.